The spirituality of student teachers: a blind spot? - J. de Klerk-Luttig (Koers : Bulletin for Christian Scholarship, 2008)
This article, which is framed in a Christian perspective, argues the importance of creating a space to nurture the spirituality of student teachers since that colours the entire educational experience. Teacher education ought to be done in an environment which is conducive not only to intellectual growth, but also to spiritual growth. First, the concept of spirituality is briefly explained. The particular experiences of a lecturer in the Philosophy of Education, who is attempting to provide support for the spiritual dimension of students by challenging them to explore some of the fundamental questions of life, form the central part of the article. Ways are suggested of not only acknowledging the spirituality of education students, but also nurturing and deepening it. Finally, suggestions for further research are outlined.